2021
DOI: 10.1371/journal.pone.0258138
|View full text |Cite
|
Sign up to set email alerts
|

Association between common polymorphisms in IL-1 and TNFα and risk of peri-implant disease: A meta-analysis

Abstract: Background Pro-inflammatory cytokines interleukin-1 (IL-1) and tumor necrosis factor α (TNFα) play important roles in host immune response and bone metabolism during dental implant osseointegration. Whether the functional polymorphisms in IL-1α, IL-1β and TNFα were associated with peri-implant disease was unclear, and we performed the present meta-analysis for this purpose. Methods Eligible studies investigating IL-1α C-889T, IL-1β C+3954T and C-511T, TNFα G-308A, composite genotype of IL-1α C-889T and IL-1β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 59 publications
2
18
0
Order By: Relevance
“…In the present study, it was found that individuals who had the polymorphism in the IL-1B +3954 had an almost twice higher risk of developing peri-implantitis (OR 1.986). This result is in agreement with a meta-analysis performed by Jin et al where the association between IL-1A −889, ILB +3954, IL-1B -511, composite genotype of IL-1A −889 and ILB +3954, and TNF-α −308 and risk of peri-implant disease (PID) was evaluated [29]. The PID included implant failure/loss, marginal bone loss and peri-implantitis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, it was found that individuals who had the polymorphism in the IL-1B +3954 had an almost twice higher risk of developing peri-implantitis (OR 1.986). This result is in agreement with a meta-analysis performed by Jin et al where the association between IL-1A −889, ILB +3954, IL-1B -511, composite genotype of IL-1A −889 and ILB +3954, and TNF-α −308 and risk of peri-implant disease (PID) was evaluated [29]. The PID included implant failure/loss, marginal bone loss and peri-implantitis.…”
Section: Discussionsupporting
confidence: 91%
“…Some of them do not refer to confounding variables such as periodontal condition, ethnicity and smoking habits. Furthermore, many studies, including published systematic reviews, assess the relationship of these polymorphisms with the peri-implant disease, pooling in the same group patients with bone loss, implant loss, and peri-implantitis [27][28][29]. However, peri-implant tissue health can exist around implants with variable levels of bone support [6].…”
Section: Introductionmentioning
confidence: 99%
“…The close association of the four genetic variants IL-1a, IL-1b, TNF-a and IL-1RN with the risk of peri-implantitis development or implant loss has been demonstrated in a large number of worldwide association studies and was also confirmed in meta-analyses [ 72 , 73 ]. It was concluded that functional polymorphisms of IL-a < (C-889 T), IL-b (C + 3954 T and C-511 T) and composite genotype of IL-1 are valuable as predictive markers for peri-implant disease.…”
Section: Discussionmentioning
confidence: 83%
“…A recent meta-analysis found that carriers of positive genotype of IL-1A-889 and IL-1B+3954 had 1.95-fold risk of peri-implant disease (which included implant failure/loss, marginal bone loss and peri-implantitis). The authors concluded that the positive genotype of IL-1 can be used as predictive marker for peri-implant disease ( Jin, Teng & Cheng, 2021 ).…”
Section: Discussionmentioning
confidence: 99%